2003
DOI: 10.1007/s15010-002-3100-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Rates of Viral Hepatitis Infections in Refugee Kurds from Iraq and Turkey

Abstract: This survey shows a high prevalence of enterically transmitted viral hepatitis in Kurds. HBV infection is moderately endemic, while the prevalence of HCV infection is low. There is a need for a universal immunization strategy for HBV in the Kurd population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 23 publications
2
21
1
2
Order By: Relevance
“…Moreover, the results of a study on blood donors in industrial countries namely United States, England, France, Germany, Spain, and Italy illustrated anti-HEV sero-positivity rates of 1.2% -2.2% (20). The prevalence of hepatitis E in neighboring countries of Iran including Turkey, Kurdistan of Iraq, and Pakistan has been also reported to be respectively 3.8% (21), 14.8% (22), and 17.5% (22). The prevalence of the infection among blood donors in Saudi Arabia has been as high as 33.3% (23).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the results of a study on blood donors in industrial countries namely United States, England, France, Germany, Spain, and Italy illustrated anti-HEV sero-positivity rates of 1.2% -2.2% (20). The prevalence of hepatitis E in neighboring countries of Iran including Turkey, Kurdistan of Iraq, and Pakistan has been also reported to be respectively 3.8% (21), 14.8% (22), and 17.5% (22). The prevalence of the infection among blood donors in Saudi Arabia has been as high as 33.3% (23).…”
Section: Discussionmentioning
confidence: 99%
“…Small-scale studies in specific populations have found rates of infection ranging from 0.1% to 8%. 7,[11][12][13] Currently, recommended screening practices for refugees arriving in the United States correspond to CDC recommendations for the general U.S. population (http://refugeehealthta.org/chronic-hepatitis-infection/).…”
Section: Introductionmentioning
confidence: 99%
“…Precise information on the prevalence of certain infectious diseases in currently turbulent regions of the world is not always available. The paper of Chironna et al in this issue of IN-FECTION improves our knowledge about the prevalence of viral hepatitis in refugee Kurds from Iraq and Turkey [1]. This paper is very timely.…”
Section: Ruefmentioning
confidence: 85%